Sociopragmatics of Insulting and Insulting Speech by Netizens in the Comments Column of TikTok Accounts - Kastri Elmi; Fitrah; Sonia Setiawati; Meirita Wulansari Kemit; Hermandra (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study examines the phenomenon of insulting and ridiculing utterances expressed by Indonesian netizens in the comment section of the TikTok account @golkar.indonesia, particularly those directed at public figure Bahlil Lahadalia. This phenomenon reflects a shift in the communication style of the young generation in digital spaces, where slang, sarcasm, and humor are used as means of social expression and political criticism. The research employs a qualitative descriptive method with a sociopragmatic approach, combining social and pragmatic perspectives in analyzing language use. The data were collected through documentation of user comments on TikTok videos featuring Bahlil Lahadalia and were analyzed based on their forms, functions, and social meanings. The results show that insulting and ridiculing utterances are not merely violations of language etiquette but also serve as symbolic resistance toward power and as a form of non-formal political participation. Netizens use linguistic strategies such as irony, sarcastic humor, and rhetorical questioning to express criticism indirectly yet sharply. The utterances found include basic words, phrases, clauses, and wordplay characterized by informal, youthful slang typical of social media interaction. From a sociopragmatic perspective, this phenomenon indicates a shift in politeness norms, where negative expressions are disguised in humor to remain socially acceptable. Therefore, TikTok has become a new arena of digital political communication, where language functions not only as a tool of interaction but also as a medium of criticism, identity, and social expression among youth.